CTNI-49. EARLY SIGNAL OF ACTIVITY FROM A PHASE 2 STUDY OF ST101, A FIRST-IN-CLASS PEPTIDE ANTAGONIST OF CCAAT/ENHANCER-BINDING PROTEIN Β (C/EBPΒ), IN RECURRENT GLIOBLASTOMA (GBM). (14th November 2022) - Iwamoto, Fabio; Gondi, Vinai; Butowski, Nicholas; Falchook, Gerald; Williams, Anja; Peters, Katherine B; Evans, Jeff; Lakhani, Nehal; McKean, Meredith; Symeonides, Stefan; Ellingson, Benjamin; Rotolo, Jim; et al.
Abstract: BACKGROUND: C/EBPβ is a transcription factor that is active during embryofetal development but held in an inactive state in most mature cells (Zahnow 2009). C/EBPβ activates a proliferation/survival gene signature in multiple cancers, where it inversely correlates with disease prognosis and survival. ST101 is a cell-penetrating peptide antagonist of C/EBPβ. ST101 exposure leads to selective tumor cell death in multiple human cancer cell lines, including GBM, without impacting normal cell viability. In vivo, ST101 displays rapid uptake into multiple organs, the ability to cross the blood-brain barrier, and a long plasma half-life due to its resistance to degradation. It has potent anti-tumor activity in multiple GBM models, as a single agent or in combination, which supported moving into clinical development. TRIAL DESIGN: This phase 2 study is enrolling adult patients with GBM that has recurred or progressed after one standard treatment regimen (surgery, radiotherapy +/-temozolomide). Patients require measurable disease at baseline and at least 3 months from prior radiotherapy. Subjects receive the recommended phase 2 dose of ST101 (500mg IV weekly). Recruitment in the phase 2 portion of this trial began in January, 2022. RESULTS: As of June 1, 2022, 14 GBM patients were enrolled. One patient has a confirmed mRANO partial response (PR) after 18 weeks of therapy, seven patients have not reached the first on-study assessment and six patients progressed. The median duration of therapy was 5 weeks. ST101 has a favorable safety profile with minor infusion related reactions being the most common adverse event. Based on the confirmed PR, the GBM cohort will be expanded. CONCLUSION: This first-in-class C/EBPβ inhibitor, ST101, showed an early signal of activity in recurrent GBM. More extensive follow-up and clinical experience will be presented as this trial expands and matures.